Atlas fonológico-fonético das vogais médias pretônicas em Goiás - Soares, Thaynara Cardoso (2022)
Goiás is a state located in the center-west region of Brazil and its formation took place with the arrival of the pioneers initially in search of Indians, but, with the discovery of gold, the state received numerous families from different states of Brazil, mainly from of São Paulo and Minas Gerais. To know the variations of pretonic mid-vowels in the state of Goiás, we carried out in this work the mapping of mid-stressed vowels in pretonic position. Therefore, for the development of the research, we used Dialectology as a theoretical framework under the method of Geolinguistics and Phonetics-Phonology. Both theories are extremely important for the development of this work. To develop this research, we used the corpus of the project Laboratório da Língua de Goiás (LABOLLINGO), and in it, we selected two informants: corresponding one female and one male, totaling 48 informants from the 24 cities studied. Thus, it is worth mentioning that this work makes use of data taken from the audiovisual collection of speech in Goiás – AUFAGO; collected for the development of the Linguistic Atlas of Goiás - ALINGO. After data selection and phonetic transcriptions, the phonetic maps were prepared. Thus, obtaining a total of 11 linguistic maps, from which we observed that from all the studied locations, there is a predominance of the higher vowels [i] and [u], followed by the higher mid vowels [e] and [o].